Assessment of interprofessional professionalism of surgical residents and workers in operating units in teaching hospitals: A cross-sectional study - Fatemeh Keshmiri (Zanjan University of Medical Sciences and Health Services, 2022)
Background & Objective: Professionalism and interprofessional cooperation are essential capabilities of health team members. Educational systems must use an appropriate approach for training and evaluating these capabilities. The present study aimed to investigate the adherence of surgical residents and personnel to interprofessional professionalism behavior in the operating units using the interprofessional professionalism Assessment (IPA). Materials & Methods: This cross-sectional study was conducted at Shahid Sadoughi University of Medical Sciences from 2019 to 2020. The performance of surgical team members, including 113 residents, surgical technologists (operating room), and anesthesia technicians, was evaluated using the interprofessional professionalism assessment tool (IPA). Data were analyzed using descriptive (mean and standard deviation) and analytical (ANOVA, Chi-square) tests. Results: The score of interprofessional professionalism behavior of the team members in the operating units were reported as 1.16 ± 0.27 out of 5. No significant difference (F=0.24, P=0.333) was observed between the participants' scores in different disciplines. The lowest scores of the participants in the "excellent" range were 1.04±0.31 out of 5. Conclusion: The results showed that interprofessional professionalism behavior among the participants was weak. It is suggested that planning for formal curriculum and continuous evaluation of adherence to improve the interprofessional behavior among surgical team members.